2007
DOI: 10.1007/s10620-007-9855-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient Knowledge and Perspective on Irritable Bowel Syndrome: Development of a Survey Instrument

Abstract: The survey instrument was found to be reliable, valid and usable. It provides descriptive data on patient knowledge, fears, and concerns surrounding irritable bowel syndrome. This easily administered questionnaire should provide novel information to improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…[36] It is encouraging that the vast majority of physicians surveyed knew the clinical presentation of IBS Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[36] It is encouraging that the vast majority of physicians surveyed knew the clinical presentation of IBS Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…[3616] Unfortunately, we found that more than a third of the physicians (35.4%; 15 males, and 8 females) were not sure how to diagnose IBS and this could contribute to a lack of diagnostic confidence and may result in unnecessary investigations. It was surprising that when asked about investigations, nearly half of the physicians surveyed suggested a complete blood count and ESR with stool examination, colonoscopy, and abdominal radiologic imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients had the most educational interest in topics on: 1) foods to avoid (63.3%); 2) causes of IBS (62%); 3) coping strategies (59.4%); 4) medications (55.2%); 5) whether they would have to live with IBS for life; (51.6%); and 6) research studies (48.6%). Further, patients indicated that they would like their health care providers to refer them to another source for additional information (95.8%); to answer questions (95.9%); to listen (94.4%); to provide information about IBS studies and medications (94%); to provide support (88.6%); and hope (82.1%) [23,24]. In regards to desired sources for obtaining medical information, "my doctor" was on top of patients' lists, followed by "the internet," "a pharmacist," and "brochures" [12,25].…”
mentioning
confidence: 99%